(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background Zika (ZIKV), a flavivirus firstly identified in rhesus monkeys in Zika Forest of Uganda, in 1947, is an emerging virus transmitted mainly by mosquitoes bites. Due to ZIKV adaptation to humans, that can maintain a mosquito-human-mosquito transmission cycle, it is essential to know the attitudes, knowledge and behaviours of general population regarding ZIKV prevention. Our main study aims were to develop and validate a questionnaire administered to the general population, in order to assess attitudes, knowledge and behaviours around prevention and control of Zika infection. Methods A questionnaire was developed based on a comprehensive review of the extant literature, pre-existing questionnaires and experts focus groups. Results The final, validation version of the questionnaire comprised 8 items, with good psychometric properties (Cronbach’s alpha of 0.81). Overall test/re-test concordance was 0.86, ranging from 0.76 to 0.94 according to each item. Conclusion In conclusion, the questionnaire seems to be an appropriate and useful tool to detect cognitive gaps concerning behaviours responsible for possible transmissions of the disease, even in a non-endemic country such as Italy. Future analysis will explore the factorial structure of the questionnaire as well as knowledge, beliefs and attitudes concerning ZIKV among Italian general population.